Tissue structural analysis for internal browning sweet potatoes using magnetic resonance imaging and bio-electrochemical impedance spectroscopy. (July 2023) - Watanabe, Takashi; Sekiyama, Yasuyo; Kawamura, Takeshi; Fukuda, Yayoi; Nagata, Masayasu
Abstract: Occurrence of internal browning in sweet potato tuber has recently been confirmed, and its chemical and bacterial characteristics have been reported. However, the structural characteristics of such tissues are unknown. We investigated the tissue structural characteristics inside a browning sweet potato through magnetic resonance imaging (MRI) and bio-electrochemical impedance spectroscopy (BIS) and the relationship was discussed. The high-resolution proton density-weighted (PDW) and proton spin–spin relaxation time ( T 2 )-weighted (T2W) images of cutting out samples obtained from micro-imaging revealed changes in the physical structure surrounding the browning tissues. The T 2 distribution maps of the same browning samples assumed the changes in the water distribution and water mobility, which generally changes under the influence of solutes, such as metabolites, starch, protein, and metal ions. BIS further confirmed the variation in the distribution of electrolytes in the tissues. MRI may provide a non-destructive assessment of the internal browning of whole sweet potatoes. Highlights: Cell tissues of internal browning sweet potatoes were assessed by MRI and BIS. MR images clearly showed the differences between the normal and browning samples. BIS showed that distribution of electrolytes in the browning tissues was changed. MRI could nondestructively evaluate the internal browning of whole sweet potatoes.